Assessment practices of educational psychologists and other educational professionals. Issue 4 (2nd October 2022) - Atkinson, Cathy; Barrow, Joanna; Norris, Sarah
ABSTRACT: Assessment is one of the five functions of the educational psychologist's (EP's) role, yet there is a dearth of research exploring its distinctive contribution to school-based practice, and a lack of definition about what it is. In this study, the assessment practices of EPs were compared with those of other educational professionals who had achieved certification for competence in educational testing. Data were analysed using descriptive and inferential statistics, with patterns emerging which indicated that, while there is some overlap, assessment practices of EPs and other educational professionals often have different foci. Specifically, evidence suggests that EPs offer a broader, more holistic perspective with strong emphasis on the social and emotional wellbeing of the child. Additionally, other practitioners typically have a more school-orientated focus, for example, testing for exam access arrangements, reflecting their professional role. Implications are discussed, particularly in relation to the distinctive contribution to EP assessment.